BRIDGING SOCIAL CAPITAL KADER PEMBERDAYAAN DAN KESEJAHTERAAN KELUARGA DALAM PENANGANAN STUNTING DI DESA SUKARASA KECAMATAN MALANGBONG KABUPATEN GARUT - Fahrul Fauji, Yohandi; Aritonang, Admiral Nelson; Aribowo, Aribowo (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2024)
Handling the issue of stunting is one of the national strategic issues in Indonesia. The stunting rate in Kabupaten Garut in 2023rd was 21.3%, with a target reduction to below 14%. In 2018th Desa Sukarasa was categorized as one of the 20 villages with the highest stunting rates, referred to as stunting focus locations. However, in 2022nd Desa Sukarasa successfully exited the status of a stunting focus location because of efforts the Pemberdayaan dan Kesejaheraan Keluarga (PKK) Cadres in utilizing interaction and collaboration with their social networks as a component of bridging social capital. This study examines the interactions, which consist of information exchange, communication media, and cooperation and collaborations established by the PKK Cadres with their social networks. This research employs a qualitative method, with data collection through in-depth interviews, focus group discussion (FGD), and documentation studies. The results show that the interaction between the PKK Cadres and their social networks involves exchanging information about stunting, using direct communication media, and leveraging technological advancements. Additionally, cooperation and collaboration have been established to organize programs and activities to reduce the percentage of stunting in Desa Sukarasa. The outcomes of these interactions and collaborations include increased knowledge and expand access to asset ownership for the PKK, which successfully removed Desa Sukarasa from the stunting focus locations status. However, in terms of networking capabilities, the PKK Cadres have not fully maximized building social networks outside the government's health sector